An extraordinary pulmonary artery involvement in granulomatosis with polyangiitis - Alkhdairi, Ahmad A.; Alharbi, Ayman A. (International Journal of Advances in Medicine, 2021)
Granulomatosis with polyangiitis (GPA) is an autoimmune mediated systemic disease and characterized by pauci-immune vasculitis mainly of small and medium vessels with typical necrotizing granulomatous lesions in the affected tissues. A 44 year old lady who was known to have GPA presented with unusual presentation of its category with extraordinary large vessels involvement including pulmonary arteries and her condition improved with immunosuppressive therapy. We reported this case, to improve the awareness about other overlapping categories of vessels vasculitis that may involve large vessels and main pulmonary arteries and to avoid misdiagnosing these patients with category of classical large vessels vasculitis.